Strategi Mengintegrasikan Energi Terbarukan, Inovasi Teknologi, dan Konservasi Hutan Sebagai Pembangunan Berkelanjutan di Indonesia - Nelly; Susanti; Radhiana; Fitriliana; Nurfiani Syamsuddin; Marlina (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This literature review investigates the potential synergies between forest conservation, technological innovation, and renewable energy in order to promote sustainable development in Indonesia. Indonesia can cut fossil fuel use and carbon emissions with its solar, wind, hydro, and biomass energy potential. This study examines the economic and environmental effects of renewable energy adoption and how smart grids, energy storage, and drone and satellite-based monitoring can conserve forests. Lack of empirical data on the long-term implications of this integration is shown by study gaps. This article offers pragmatic policy suggestions and implementation tactics to maximise financial and environmental benefits. A Central Kalimantan REDD+ project reduced deforestation, protected wildlife, and boosted local economy. This study should help governments and industry establish sustainable policies and raise public understanding of the necessity of integrating renewable energy, technology, and forest protection. If all stakeholders agree, this integration can become a paradigm for sustainable development in Indonesia, ensuring a brighter, greener future.